Real‐World Treatment Patterns and Associated Outcomes in Patients With Resectable Early‐Stage Non‐Small Cell Lung Cancer: The THASSOS International Study - Kumar Prabhash; Rebecca Moor; Tuncay Göksel; Jonathan Nyaw; Abdullah Khalaf Altwairgi; Francisco Gonzalez; Elsayed Mohamed; Pushpalatha Kantharaju; Farah Sadek (Thoracic Cancer)
ABSTRACT Background THASSOS‐INTL (NCT04808050), a multinational, retrospective study, evaluated treatment patterns and associated outcomes in patients with early‐stage non‐small cell lung cancer (NSCLC) from seven countries in the Asia‐Pacific and the Middle‐East and Africa. Methods Eligible adult patients (≥ 18 years) with resectable clinical stage (CS) IA‐IIIB NSCLC (7th AJCC) diagnosed from 01/01/2013 to 31/12/2017 were followed until death, last recorded clinical visit, or 31/12/2020 (data cut‐off). Results Of 755 patients (CS I: 30.6%, CS II: 35.0%, CS III: 34.2%) with a median age of 62 [range: 56–69] years enrolled, 69.3% were male, and 75.0% were current/ex‐smokers. Of 24.2% of patients tested for EGFR, 28.4% (52/183) were positive, while 23/44 patients tested (52.3%) had PD‐L1 expression (≥ 1%: 16; unknown: 7). Overall, 82.9% had surgery, of whom 39.1% (245/626) had surgery alone; 21.1% received neoadjuvant therapy, 51.1% received adjuvant therapy, and 5.8% received both; 11.2% (58/519) patients received targeted therapy (adjuvant: 47 patients; neoadjuvant: 11 patients), and 4.6% (24/519) received immunotherapy (adjuvant: 22 patients; neoadjuvant: 2 patients). The 3‐year survival was 77.4% with a median overall survival (mOS) of 7.5 (95% confidence interval [CI]: 6.7–NE) years, with the highest mOS recorded with adjuvant therapy (7.5 [95% CI: 7.0–NE] years). Conclusions This real‐world study showed > 50% use of adjuvant therapy per guideline recommendations but poor use of neoadjuvant therapy. Biomarker testing at diagnosis was low, reflecting the study period being before targeted and immunotherapies. With recent approvals of newer (neo)adjuvant agents, a multidisciplinary approach is needed for better treatment decisions to improve the prognosis of early‐stage NSCLC.